(untitled) (Ecological Bulletin of Kryvyi Rih District, 2021)
With the help of ecological and conomorphic analysis of vegetation using the data “Ecoflora of Ukraine” according to the principles developed by O. L. Belgard (1960) found that in the plant groups of the Kryvyi Rih urban complex there are 74 species belonging to 63 genera and 22 families. The most common members of such families as Asteraceae, Fabaceae, Brassic´aceae, Poaceae, Rosaceae, Apiaceae, Plantaginaceae, Salicaceae. The base of plant groups of the Kryvyi Rih urban-industrial complex is created by ruderants (51.27% of the total number of species) and stepants (21.61%). In addition, among the life forms according to the classification K. Raunkier (1934) is dominated by hemicryptophytes (50% of the total number of species) and therophytes (25.9%). In terms of preferences for water regime, the most numerous are xeromesophytes (53% of the total number of plants) and mesoxerophytes (29.4%). The groups are dominated by heliophytes (55.0%) and mesotrophs (60.6%). Ecological characteristics of the vegetation of research areas according to the system of ecomorphs O. L. Belgard (1950) found that the dominant position among coenomorphs belongs to ruderants (51.27% of the total number of species) and steppes (21.61%). The sites in the Metallurgical District are dominated by ruderants and steppes. The climamorphic spectrum showed a quantitative predominance in the composition of plant groups of hemicryptophytes (50% of the total number of species) and therophytes (25.9%). In general, all areas are dominated by plants that die at the beginning of the unfavorable period to ground level or survive it exclusively in the form of seeds. This is one of the effective physiological mechanisms of preservation and increase in the number of species composition in the areas. Analysis of hygromorphic spectra revealed the dominant role of transitional forms from xerophytes to mesophytes. Xeromesophytes represent almost 53% of the total number of plants, and mesoxerophytes account for 29.4%. There are no xerophytes in plot 3. The number of heliophytes (55.0% of the total number of species) is the largest among heliomorphs of all research sites. Among tropomorphs, the most numerous are mesotrophs (60.6% of the total number of species), megatrophs and oligotrophs are represented in equal numbers, namely 19%. Thus, the most numerous ecomorphs in the phytocenoses of research sites with different levels of pollution are ruderants, hemicryptophytes, xeromesophytes, heliophytes and mesotrophs. Stepants, solvants, therophytes, mesophytes, megatrophs and oligotrophs have a stable presence.